A study on the factors that influence job satisfaction among lecturers in Universiti Utara Malaysia - Kok, Sau Yee (2015)
Job satisfaction has been an increasingly researched field of study since the past research shown the important to the organization as a whole. Despite the increase in attention given to the study of workplace satisfaction, there is still question on the relationship and affects to the satisfaction. This study tries to identify the relationship between the salary, job stress, career promotion and working environment in the academic community towards job satisfaction of the lecturers. The current research has been conducted among 226 lecturers in Universiti Utara Malaysia (UUM). A questionnaire survey based research was used to collect data and analyzed using Pearson correlation and linear regression to identify the relationship and test the hypothesis. The findings of this study indicate, that there is a significant and positive relationship between salary, job stress, career promotion, working environment and job satisfaction. Job stress was found to be not significant in affecting the job satisfaction of lecturers.